Fighting the Financial Crisis in Greece: The Privileged Company to Protect Production and Trade in Currants (1905) as International Bank Cooperation - Schönhärl, Korinna (The Historical Review/La Revue Historique, 2013)
The global economic crisis in the 1890s affected the economy of Greece severely, and in 1893 the Greek State had to stop servicing its foreign debt. Part of the problem was the lack of diversity of Greek agricultural production, which was focused on raisins and currants (especially flavourful raisins, grown exclusively in the area around Corinth) for export. The collapse of market prices for this good seriously affected the Greek treasury and society in the growing regions. The Greek government responded by trying to withhold part of the harvest in fertile years to stabilise world market prices. Plans to organise a monopoly company for the currant trade necessitated high sums of capital from abroad. This article investigates the question of how foreign bankers in London (Hambro & Son, Emile Erlanger) and Paris (Banque de l’Union Parisienne) could be convinced to participate in the project. Which factors allowed foreign bankers to trust in the Greek national economy despite its poor reputation? What factors influenced their risk management? The focus is on the role of Greek brokers in persuading the foreigners to invest in Greece, especially the role played by Ioannis Pesmazoglou, the director of the young and innovative Bank of Athens.